(untitled) (Journal of Medical & Health Sciences Review, 2025)
INTRODUCTION: Attention Deficit Hyperactivity Disorder (ADHD) and Lower Urinary Tract Dysfunction (LUTD) are common pediatric conditions that can significantly affect a child’s quality of life. In developing countries, the cooccurrence of these conditions is often overlooked. This study investigates the prevalence and association of ADHD and LUTD among school-going children in a developing country, aiming to highlight the need for integrated diagnostic and management approaches. METHOD: A cross-sectional study was conducted involving 500 school-going children aged 6-12 years. ADHD was diagnosed using Conner’s’ Parent Rating Scale, while LUTD was assessed through a validated questionnaire and clinical evaluations. Data were analyzed using chi-square tests and logistic regression to determine the association between ADHD and LUTD, adjusting for potential confounders like age, sex, and socioeconomic status. RESULTS: The prevalence of ADHD among the participants was found to be 12%, while 15% of the children had LUTD. Notably, 7% of the children exhibited both ADHD and LUTD, indicating a significant overlap. Children with ADHD had a 2.5 times higher likelihood of having LUTD compared to their non-ADHD peers (p < 0.05). Logistic regression analysis confirmed that ADHD was an independent risk factor for LUTD after controlling for confounders. CONCLUSION: The study reveals a significant association between ADHD and LUTD in school-going children in a developing country. These findings underscore the importance of screening for LUTD in children diagnosed with ADHD and vice versa, to ensure comprehensive care and better management outcomes.